Drug-associated progressive multifocal leukoencephalopathy in multiple sclerosis patients. (July 2019) - Oshima, Yasuo; Tanimoto, Tetsuya; Yuji, Koichiro; Tojo, Arinobu
Objective: To investigate characteristics of multifocal leukoencephalopathy (PML) in multiple sclerosis (MS) patients associated with drugs other than natalizumab since our experience in other disease-modifying drugs (DMD) is still limited. Methods: This is a descriptive observational study within the FAERS database, registered between July 2015 and June 2017. Results: The primary cohort for the analysis consisted of 100, 921 MS patients (mean (standard deviation (sd)) age, 48.9 (12.8) years, 20.9% male). Among them 786 (0.78%) developed PML. The adjusted odds ratio of PML for each drug was as follows; natalizumab 115.72 (95% CI; 83.83, 159.74), fingolimod 4.98 (3.64, 6.81) followed by dimethyl fumarate 1.77 (1.2, 2.62) and rituximab 3.22 (1.07, 9.72). The median time from the start of suspected drugs to the onset of PML for natalizumab and other agents were 1463 and 178 days, respectively. The proportion of PML appeared higher in Japan (2.4%) compared to that in the United States (0.24%). Conclusion: The reporting proportion of PML was relatively higher in natalizumab followed by fingolimod, dimethyl fumarate and rituximab. Other characteristics of PML associated with DMDs, including the time to onset and differences in reporting among countries, are described.